Conocimiento, aptitudes y prácticas sobre lactancia materna en madres adolescentes con niños de 0 a 12 meses de edad que acuden al servicio de consulta externa de pediatría del Hospital Isidro Ayora de la ciudad de Loja en el periodo marzo agosto del 2014 - Armijos Montaño, Kevin Marlon (2015)
This research was conducted at the Isidro Ayora Hospital in the city of Loja, during the period from March to August 2014, with the participation of teenage mothers who attended the outpatient service; the objective being to determine the knowledge, attitudes and practices about breastfeeding. This was a qualitative and quantitative, descriptive, cross-sectional study; the study population consisted of 67 teenage mothers with children 0-12 months of age, which derived variables based on the objectives questionnaire was applied. As for the results of the research, 69% have enough knowledge and 31% enough; 52% own skills favorable and 48% unfavorable; 60% of exclusive breastfeeding practices are adequate and 40% inadequate; 77% of mothers who supplemented or abandoned breastfeeding practices are inadequate and 23% good practices. We conclude that teenage mothers have insufficient knowledge because they have not received information about breastfeeding; under unfavorable skills affecting breastfeeding practices among adolescents. Keywords: Breastfeeding, knowledge, skills, practices.